2012
DOI: 10.1371/journal.pmed.1001265
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Community-Based Nursing Intervention on Mortality in Chronically Ill Older Adults: A Randomized Controlled Trial

Abstract: Kenneth Coburn and colleagues report findings from a randomized trial evaluating the effects of a complex nursing intervention on mortality risk among older individuals diagnosed with chronic health conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
96
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(96 citation statements)
references
References 48 publications
0
96
0
Order By: Relevance
“…Most notably, Health Quality Partners, a non-profit disease management organization in Pennsylvania, reduced hospitalization rates and overall mortality among their enrollees, though the program did not lower total costs after discounting program fees. 33 In contrast to other programs in the demonstration, care coordinators in the Health Quality Partners program provided regular in-person interaction with their assigned patients and had close relationships with their primary care clinicians. The coordinators also focused on coordinating care transitions and medication management.…”
Section: Approach 1: Complex Case Management Embedded Within Primary mentioning
confidence: 99%
“…Most notably, Health Quality Partners, a non-profit disease management organization in Pennsylvania, reduced hospitalization rates and overall mortality among their enrollees, though the program did not lower total costs after discounting program fees. 33 In contrast to other programs in the demonstration, care coordinators in the Health Quality Partners program provided regular in-person interaction with their assigned patients and had close relationships with their primary care clinicians. The coordinators also focused on coordinating care transitions and medication management.…”
Section: Approach 1: Complex Case Management Embedded Within Primary mentioning
confidence: 99%
“…With the rapid growth of diabetes prevalence in China, the burden on health care is also increasing rapidly. Evidences have shown that the community-based management of diabetes was more effective in reducing the disease-related health problems [2,3]. Therefore, an appropriate management model for diabetes care in communities is the key for the prevention and control of diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…A nurse-led care coordination program in Doylestown, Pennsylvania has demonstrated improved outcomes and lower expenditures among Medicare beneficiaries for over 10 years. 8 This randomized control trial demonstrated a 25% lower mortality risk, and in the highest risk population-defined as ≥1 admission in the past year along with a diagnosis of heart failure, coronary disease, or COPD-a 36% reduction in Part A and B Medicare expenditures. 8,9 The early success of these and other emerging programs is guiding policy.…”
mentioning
confidence: 91%
“…8 This randomized control trial demonstrated a 25% lower mortality risk, and in the highest risk population-defined as ≥1 admission in the past year along with a diagnosis of heart failure, coronary disease, or COPD-a 36% reduction in Part A and B Medicare expenditures. 8,9 The early success of these and other emerging programs is guiding policy. An SU learning collaborative not only developed key policy recommendations, but is working at the state level to advocate for reform.…”
mentioning
confidence: 91%
See 1 more Smart Citation